Goal directed fluid therapy for major liver resection: A multicentre randomized controlled trial. (September 2019) - Weinberg, Laurence; Ianno, Damian; Churilov, Leonid; Mcguigan, Steven; Mackley, Lois; Banting, Jonathan; Shen, Shi Hong; Riedel, Bernhard; Nikfarjam, Mehrdad; Christophi, Chris
Abstract: Background: The effect a restrictive goal directed therapy (GDT) fluid protocol combined with an enhanced recovery after surgery (ERAS) programme on hospital stay for patients undergoing major liver resection is unknown. Methods: We conducted a multicentre randomized controlled pilot trial evaluating whether a patient-specific, surgery-specific intraoperative restrictive fluid optimization algorithm would improve duration of hospital stay and reduce perioperative fluid related complications. Results: Forty-eight participants were enrolled. The median (IQR) length of hospital stay was 7.0 days (7.0:8.0) days in the restrictive fluid optimization algorithm group (Restrict group) vs. 8.0 days (6.0:10.0) in the conventional care group (Conventional group) (Incidence rate ratio 0.85; 95% Confidence Interval 0.71:1.1; p = 0.17). No statistically significant difference in expected number of complications per patient between groups was identified (IRR 0.85; 95%CI: 0.45–1.60; p = 0.60). Patients in the Restrict group had lower intraoperative fluid balances: 808 mL (571:1565) vs. 1345 mL (900:1983) (p = 0.04) and received a lower volume of fluid per kg/hour intraoperatively: 4.3 mL/kg/hr (2.6:5.8) vs. 6.0 mL/kg/hr (4.2:7.6); p = 0.03. No significant differences in the proportion of patients who received vasoactive drugs intraoperatively (p = 0.56) was observed. Conclusion: In high-volume hepatobiliary surgical units, the addition of a fluid restrictive intraoperative cardiac output-guided algorithm, combined with a standard ERAS protocol did not significantly reduce length of hospital stay or fluid related complications. Our findings are hypothesis-generating and a larger confirmatory study may be justified. Highlights: Major liver resection is a complex procedure with up to 40% patients experiencing complications. Optimisation of perfusion and oxygen delivery to all organs remain the cornerstone of best hemodynamic care. Traditionally, a low central venous pressure strategy during major liver resection has been used to reduce venous bleeding. The impact of a restrictive cardiac output fluid optimisation algorithm during major liver surgery is unknown. After major hepatobiliary surgery, a fluid restrictive algorithm did not reduce length of hospital stay or complications.